If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 3) + 25 = 46 Reorder the terms: (3 + x) + 25 = 46 Remove parenthesis around (3 + x) 3 + x + 25 = 46 Reorder the terms: 3 + 25 + x = 46 Combine like terms: 3 + 25 = 28 28 + x = 46 Solving 28 + x = 46 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-28' to each side of the equation. 28 + -28 + x = 46 + -28 Combine like terms: 28 + -28 = 0 0 + x = 46 + -28 x = 46 + -28 Combine like terms: 46 + -28 = 18 x = 18 Simplifying x = 18
| 2(-3+5n)-9(-6n-4)= | | A=sqrt(5/CB) | | 9m^4n^2-16=0 | | sqrt(x+4)+2=x | | 3/x=2/y-1/z | | -3+2(4-7)= | | V/14-v/49=1/14 | | 6x^2+11xy+4y^2= | | 1.2x^2-7/6x=1 | | y=1/6x^3 | | 4y-9+y=26+2y-4y | | 3(2-5)+4= | | 8y-3x=20 | | 4y-9+y=26+2y+4y | | -9n-6+12n+40=22 | | 8x-3+5x+1= | | X(2x+8)=240 | | X^2=-16+16x | | (5a+17)(4a)= | | 5+19-x=8 | | 5+19+x=8 | | C=xy^9/t | | 8p=-4-4p | | 5(x-2)-2(3x+1)-4(1-2x)+x= | | -2x+12=-36 | | 6(-2z+5)=19z+16 | | 4*(3x-4)=44 | | 4x+15=2x+14 | | =12(p+4) | | 5x+20=2x-6 | | 6y-12-3y-3=8 | | 3m*n= |